2022
DOI: 10.3389/fendo.2022.805636
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Maternal First-Trimester Low Body Mass Index Against Macrosomia: A 10-Year Cross-Sectional Study

Abstract: ObjectiveWe aimed to assess whether maternal first-trimester low body mass index (BMI) has a protective effect against macrosomia.MethodsThis was a cross-sectional study from January 1, 2011, to June 30, 2021, and 84,900 participants were included. The predictive performance of maternal first-trimester and parental pre-pregnancy BMI for macrosomia was assessed using the area under the receiver-operating characteristics curve (AUC). Multivariate logistic regression analyses were performed to evaluate the indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…An increased pre-pregnancy BMI and excessive maternal weight gain in pregnancy have been recognized as prerequisites for fetal macrosomia by many researchers [34][35][36][37]. Even a protective effect of low pre-pregnancy BMI in non-diabetic women has been described [38,39]. In our study groups, maternal pre-pregnancy obesity did not correlate with macrosomia, while excessive pregnancy weight gain correlated with large fetuses only when considering both groups and not the GDM category solely.…”
Section: Discussioncontrasting
confidence: 44%
“…An increased pre-pregnancy BMI and excessive maternal weight gain in pregnancy have been recognized as prerequisites for fetal macrosomia by many researchers [34][35][36][37]. Even a protective effect of low pre-pregnancy BMI in non-diabetic women has been described [38,39]. In our study groups, maternal pre-pregnancy obesity did not correlate with macrosomia, while excessive pregnancy weight gain correlated with large fetuses only when considering both groups and not the GDM category solely.…”
Section: Discussioncontrasting
confidence: 44%
“…We found that apart from a history of macrosomia, a higher prepregnancy BMI and gestational weight gain in the subsequent pregnancy were independent risk factors for macrosomia in multipara, which was consistent with previous studies [ 21 , 22 , 23 , 24 ]. A previous cohort study of 105,768 mother-child pairs [ 25 ] and a 10-year cross-sectional study of 84,900 participants [ 26 ] have reported that maternal low BMI was inversely associated with macrosomia. However, most of the previous studies were conducted on the European and American populations rather than the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…13 BMI is a widely recommended index to assess nutritional status in early pregnancy. 32 Although the association of maternal BMI in early pregnancy with adverse consequences is controversial, [33][34][35][36][37] it may be a sign of maternal health or potential fetal abnormalities, such as gestational diabetes, low birth weight, macrosomia, etc. Therefore, this study considered maternal BMI as a confounder in the adjusted LR models and did sensitivity analysis to explore and modify the association of maternal weight increase with CHD in offspring.…”
Section: Possible Reasons and Comparison With Previous Studiesmentioning
confidence: 99%